Doença de Alzheimer: modificação na funcionalidade e na capacidade antioxidante do resveratrol pela alteração nas vias de sinalização celular SIRT1 e AMPk - Luciana de Cassia Cardoso (2021)
Alzheimer's Disease (AD), considered the most prevalent dementia in aging, presents cognitive and functional decline, justified by neuroinflammation, as a result of the accumulation of senile plaques, beta amyloid and tau protein tangles, exacerbated by the accumulation of Free Radicals (RL), through Reactive Oxygen (ROS) and Nitrogen (RNS) Species. The increase of these species and/or imbalance of antioxidant defenses, such as the enzymes Catalase (CAT) and Glutathione Peroxidase (GPx), may cause Oxidative Stress (EO). Several studies indicate that this antioxidant system can fail, especially in the presence of chronic degenerative diseases. It is also observed in this condition, the Subclinical Chronic Inflammation (ICS), observed through the increase of pro-inflammatory cytokines, such as: IL6 and TNF (present in this study) and by the decrease of anti-inflammatory cytokines, such as IL10. In this context, resveratrol, a polyphenolic compound, known as a potent antioxidant and anti-inflammatory, has been the object of study in clinical medicine currently, however, it is necessary to know its activation pathways in Alzheimer's Disease. Thus, the aim of this study was to verify whether the antioxidant profile of resveratrol remains the same in leukocytes from donors with Alzheimer's (aged over 60 years), through the analysis of CAT and GPx and the SIRT1 and AMPk pathways. In addition to verifying the degree of functional capacity compared to baseline data related to EO and ICS, through the Katz Index (functional capacity). Our results show that there was a ROS reduction in cells stimulated with resveratrol also in the presence of Alzheimer's. It can be observed that resveratrol, despite acting in the group with Alzheimer's, had its antioxidant power reduced, particulary ROS and RNS, compared to the group without the disease. Polyphenol was able to increase GPx activity in cells exposed to this compound, in both groups. Analyzing the biochemical pathways, an active antioxidant behavior of AMPk was observed in leukocytes of elderly patients with Alzheimer's, however, silencing of the SIRT1 pathway was observed in this same group. Baseline values for Nitric Oxide (NO) were higher and Peroxynitrite (ONOO-) decreased in the group with the disease. The Alzheimer's group was more dependent on the Katz index. So, EO and ICS predispose to an increase in the loss of autonomy and independence.